Treatment-related symptoms among underserved women with breast cancer: the impact of physician–patient communication - Maly, Rose C. (2009)
Low-income, minority women are more likely to be undertreated for breast cancer (BC) treatment-related symptoms than whites. This study assessed the impact of patient–physician communication on symptom resolution. A cross-sectional, California statewide survey was conducted among 921 low-income women with BC. Ethnic/racial differences in BC treatment-related symptoms (pain, nausea/vomiting, depression) reporting and physician’ awareness of these symptoms were assessed by patient report. Multivariate logistic regression models were used to investigate the impact of patient–physician communication on symptom resolution. Depression was the most common symptom reported by patients (66%), yet physicians were the least aware of it (26.3%), especially among less-acculturated Latinas (18.9%) and Asian/Pacific Islanders (14%; P < 0.001). Greater patient-perceived self-efficacy in communication with physicians and greater physician awareness of the symptom positively predicted pain resolution, controlling for sociodemographic variables, comorbidity, and treatment received (AOR = 1.05, P < 0.0001; AOR = 6.12, P < 0.001). Physician awareness was a significant determinant of depression resolution (AOR = 13.46, P < 0.001). Yet patient-perceived self-efficacy played a much more important role than physicians’ awareness in nausea resolution (AOR = 1.04, P = 0.0002). Less-acculturated Latinas tended to achieve less symptom resolution than whites, while this negative impact disappeared or was moderated after patient–physician communication was considered. This study suggests that physicians under-recognized depression, especially among Latinas. The resolution of BC treatment-related symptoms can be addressed by appropriate educational interventions targeted at patient–physician communication. Effective patient–physician communication can moderate disparities in symptom resolution among Latinas, regardless of language acculturation.